Mobilizing DevOps: exploration of DevOps adoption in mobile software development - Kose, Busra Ozdenizci (Emerald Group Publishing Ltd, 2024)
PurposeThe purpose of this study is to investigate the factors facilitating and influencing the adoption of DevOps practices specifically tailored to mobile software development, with a focus on understanding the influence of mobile-specific requirements on DevOps integration.Design/methodology/approachThe study employs a qualitative methodology, including a literature review, exploratory case research and partial quantitative assessments through DORA metrics and survey applications. This approach, guided by the Technology-Organization-Environment (TOE) framework, prioritizes in-depth insights into the adoption of DevOps practices and explores strategies for integrating DevOps in mobile software development.FindingsThe research identifies several key themes specific to Mobile DevOps adoption, including tool integration issues, testing complexities, deployment challenges and security concerns. These findings underscore the necessity for tailored DevOps solutions that can effectively address the unique demands of mobile software development. The study also proposes actionable strategies to overcome these challenges, thereby enhancing the efficiency, quality and security of mobile applications.Practical implicationsThe insights gained from this study provide valuable guidance for practitioners in the mobile software development sector. By understanding and addressing the specific challenges of Mobile DevOps, organizations can improve their DevOps practices and achieve better outcomes in terms of project delivery speed, quality and security. For example, implementing robust testing strategies, investing in compatible tools and developing well-defined rollback procedures can significantly enhance Mobile DevOps effectiveness. Furthermore, incorporating continuous security measures and improving cross-functional collaboration can lead to more secure and efficient mobile application deployments.Social implicationsThis study offers valuable starting points for researching Mobile DevOps in real-world settings, based on insights from practical DevOps implementations in a single-case organization. Organizations can use this information to compare their own DevOps approaches with those of the studied organization, and can facilitate self-assessment and improvement.Originality/valueThis study contributes to the limited literature on Mobile DevOps adoption and proposing actionable strategies. By incorporating the TOE framework, it provides a comprehensive guide that enhances understanding and management of DevOps practices throughout the mobile application development lifecycle and offers significant value to practitioners and researchers alike.
Keywords: Mobile DevOps; Adoption; Maturity; Mobile software development; TOE framework; Adoption strategies